Smoking control strategies in developing countries : report of a WHO expert committee, meeting held in Geneva from 22 to 27 November 1982 - World Health Organization; World Health Organization (WHO) Expert Committee (Geneva : World Health Organization, 1983)
Highlights the harmful effects of smoking in developing countries, with emphasis on the need for concentrated action in those countries which have become the target for promotional campaigns by transnational tobacco companies. Separate sections cover the epidemiological and economic aspects of the smoking epidemic, the objectives of smoking control programmes, and legislative measures. The report concludes with recommendations for control of the smoking problem in developing countries.
Keywords: Smoking control strategies in developing countries